2016
DOI: 10.1007/s11262-015-1270-1
|View full text |Cite
|
Sign up to set email alerts
|

Human heart cell proteins interacting with a C-terminally truncated 2A protein of coxsackie B3 virus: identification by the yeast two-hybrid system

Abstract: Protein 2A is a non-structural protein of coxsackievirus B3 (CVB3), an important human pathogen that can cause a variety of human diseases. Protein 2A not only participates in viral life cycle, but also regulates host cell functions; however, the underlying mechanisms remain poorly understood. In order to better understand the molecular mechanisms of CVB3 2A's function, the yeast two-hybrid (Y2H) system was adopted to screen for CVB3 2A interactive proteins in the human heart cDNA library. Full-length 2A shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Structures interfering with host cell skeleton proteins often effectively suppress viral replication . Upregulated expression of ENO1 has been detected in several viruses including coxsackie B3 virus, dengue virus, HIV and HCV . Tripathi LP et al observed that knockdown of the ENO1 gene can significantly inhibit HCV replication in HCV 1b and 2a genotype cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Structures interfering with host cell skeleton proteins often effectively suppress viral replication . Upregulated expression of ENO1 has been detected in several viruses including coxsackie B3 virus, dengue virus, HIV and HCV . Tripathi LP et al observed that knockdown of the ENO1 gene can significantly inhibit HCV replication in HCV 1b and 2a genotype cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…36 A similar observation was made regarding the interaction between protease 2A and ENO-1, in which protease 2A blocked ENO-1 and prevented the normal function of ENO-1 during the protease 2A/ENO-1 interaction. 37 In this study, we observed an interaction between Nell-1-ΔE and ENO-1 in the extracellular spaces of two cell lines (Figure 4). Based on our existing data, we came up with the following hypothesis: Nell-1-ΔE but not full-length Nell-1 can interact with extracellular ENO-1, a cell migration-promoting factor, and blocks the functional domain of ENO-1, thereby negatively affecting the oncogenic function of ENO-1, consequently inhibiting cell migration.…”
Section: Discussionmentioning
confidence: 50%
“…Researchers have speculated that ENO‐1 might be blocked by FBXW7 when ENO‐1 interacting with FBXW7, with consequent FBXW7‐mediated suppression of the ENO‐1 function . A similar observation was made regarding the interaction between protease 2A and ENO‐1, in which protease 2A blocked ENO‐1 and prevented the normal function of ENO‐1 during the protease 2A/ENO‐1 interaction …”
Section: Discussionmentioning
confidence: 99%
“…GAL4 DNA-BD-HbMYB44 fusion proteins were expressed in yeast, and their ability to activate transcription from the GAL4 upstream activation sequence and to promote yeast growth in defective media was analyzed. The full-length ORF of HbMYB44 (HbMYB44), the N-terminal (encoding the 1st–200th aa, HbMYB44-▲N) and the C-terminal (encoding the 201st–345th aa, HbMYB44-▲C) fragments of HbMYB44 were individually fused to the GAL4 DNA-BD within the pGBKT7 vector ( Figure 3B ) and transformed into yeast strain Y2H Gold for transactivation activity analysis as previously reported ( Zhao T. et al, 2016 ). As shown in Figure 3B , all constructs (including pGBKT7-HbMYB44, pGBKT7-HbMYB44-▲N, pGBKT7-HbMYB44-▲C, negative control pGBKT7, and positive control pGBKT7-HbNAC24) grew on the SD/-Trp media, but only pGBKT7-HbNAC24, pGBKT7-HbMYB44, and pGBKT7-HbMYB44-▲C grew on the TDO media and appeared blue on TDO/X media.…”
Section: Resultsmentioning
confidence: 99%